Dual effect of axial tension force developed in catenary action during progressive collapse of 3D composite semi-rigid jointed frames. (June 2019) - Galal, Mohamed Ahmed; Bandyopadhyay, Milan; Banik, Atul Krishna
Abstract: Catenary action provides more resistance to progressive collapse of semi-rigid jointed steel frames in spite of the axial tension force developed in catenary action stage reduces the moment capacity of the connection. Dual effect of axial tension and its impact on the global structure response is not investigated yet. Limited works have been carried out on beam-column sub-assemblages. This paper studies the dual effect of axial tension developed during catenary action stage of a 3D composite multi-story building with TSD connection taking into account both material and geometry nonlinearity. ND progressive collapse analysis is carried out following the APM recommended by DoD using ABAQUS software. The results show that axial tension improves the progressive collapse resistance by 23% to 36% depending on the column removal locations whereas, the building response increases by 18% to 35% when the connection moment capacity is reduced due to the axial tension. Thus, the designers and engineers have to be cautious while depending on only the positive influence of axial tension developed in the catenary action stage because it simultaneously reduces the connection moment capacity which causes some negative effect on progressive collapse resistance. Also, this study presents a suitable and economical retrofitting scheme by providing bracing on the top floor which enhances the progressive collapse resistance.